Kebijakan Dosen Mengurangi Plagiarisme pada Karya Ilmiah Mahasiswa - Agus Hermawan (Fakulatas Dakwah IAIN Salatiga, 2019)
Abstract: The purpose of this study is to determine the lecturer's policies in reducing theplagiariasm of students' scientific work. This type of research is field researchwith a qualitative descriptive approach. policies that can be done by lecturers toreduce plagiarism including; (1). Giving a learning contract letter that containspoints prohibiting plagiarism during the learning process. (2). providingeducation and outreach about what is plagiarism. (3). Providing sanctions in theform of verbal and written reprimands so that students do not commit plagiarism.(4). Returning plagiarism papers to be revised. (5). postponement or evencancellation of value if the paper is proven to be the result of plagiarism. Theresults of this research: (1). Students who originally have a lot of copy pastebegan to decrease in percentage. (2). students who originally can not quote andparaphrase now begin to understand and apply how to quote good and right. AbstrakTujuan penelitian ini adalah untuk mengetahui kebijakan dosen dalammengurangi plagiariasme karya ilmiah mahasiswa. Jenis penelitian adalahfield research dengan pendekatan deskriptif kualitatif. Kebijakan yang bisadilakukan oleh dosen pengampu untuk mengurangi plagiarisme diantaranya;(1). Memberikan surat kontrak pembelajaran yang berisi poin laranganmelakukan plagiat selama proses pembelajaran. (2). Memberikan edukasi dansosialisasi tentang apa itu plagiarism. (3). Memberikan sanksi berupa teguranlisan dan tertulis agar mahasiswa tidak melakukan plagiat. (4). Mengembalikanmakalah hasil plagiat untuk direvisi. (5). Penundaan atau bahkan pembatalannilai apabila makalahnya terbukti hasil plagiat. Adapun hasil penelitiannya: (1).Mahasiswa yang semula banyak copy paste mulai berkurang persentasenya. (2).Mahasiswa yang semula tidak bisa mengutip dan parafrase sekarang mulaipaham dan menerapkan bagaimana cara mengutip yang baik dan benar.